Determining spectrum caps and service efficiency: A case study of mobile operators in Thailand - Srinuan, Chalita; Srinuan, Pratompong (My University, 2021)
Mobile spectrum is a crucial natural resource, which is essential in a nation's economic growth and a mobile operator's business operations and sustainability. Moreover, spectrum auctions have become a common method for spectrum allocation by telecom regulators in recent decades. In Thailand, the National Broadcasting and Telecommunications Commission (NBTC) over the past years has used a spectrum cap setting mechanism to encourage more competition in both the auctions and in the market after the auctions. This mechanism also allows regulators to determine the number of mobile operators in the market. However, regulatory mandated spectrum caps can potentially harm a large mobile operator's performance since spectrum caps can preclude large carriers from getting more necessary spectrum to support their customers' demand. Therefore, the purpose of this research was to demonstrate the effect of spectrum caps' determination using frequency allocation in Thailand as a case study. This paper employs data from Q3 2012 - Q1 2020 for the three major mobile operators in Thailand (AIS, TRUE, and DTAC) and analyzes the mean difference of six operating parameters by 1 MHz spectrum and the industry average. Results revealed that AIS was the largest carrier with the most spectrum amount, the greatest number of users, with revenue exceeding the industry average. AIS also had a statistically significant operational efficiency in all six of the evaluated dimensions. However, TRUE which is second in the total number of users in Thailand was determined to have no statistically significant operating efficiencies. Furthermore, the study determined that operators need additional spectrum so that they can increase market share through improved service quality. Finally, the empirical evidence suggests that spectrum caps when set in conjunction with each auction did not create any significant operator's efficiency problem.
Keywords: Mobile auction; Mobile spectrum; Spectrum caps; Thailand